PENGARUH KEMANDIRIAN BELAJAR TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN INFORMATIKA MATERI JARINGAN DASAR DAN INTERNET KELAS VII SMP KRISTEN CITRA BANGSA KUPANG - Maria Yoaklina Letek; Jhon Enstein; Diana Yanni Ariswati Fallo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Maria Yoaklina Letek Latuan, 2025. The Influence of Learning Independence on Student Learning Outcomes in Informatics Subjects, Basic Network and Internet Material, Grade VII, Citra Bangsa Christian Middle School, Kupang. Informatics Education Study Program, Faculty of Teacher Training and Education, Citra Bangsa University, Kupang. This study is entitled "The Effect of Learning Independence on Student Learning Outcomes in Informatics Subjects, Basic Network and Internet Materials, Grade VII of Citra Bangsa Kupang Christian Middle School". The aim is to determine the effect of learning independence on student learning outcomes in Informatics subjects, especially on Basic Network and Internet materials in Grade VII of Citra Bangsa Kupang Christian Middle School. Learning independence is one of the important factors that influence student success in understanding Informatics concepts that require logical, creative thinking skills, and problem-solving skills. This type of research is quantitative research with an associative approach. The population in this study were all grade VII students of Citra Bangsa Kupang Christian Middle School in the 2024/2025 academic year, with samples taken proportionally. Data collection techniques used questionnaires to measure the level of learning independence and learning outcome tests to determine the level of student mastery of Basic Network and Internet materials. Data analysis was carried out using a simple linear regression test to determine how much influence learning independence has on student learning outcomes. The results of the study indicate a positive and significant influence between independent learning and student learning outcomes in Informatics. This means that the higher the level of independent learning, the better the learning outcomes achieved. This finding emphasizes the importance of implementing learning strategies that encourage students to be more active, independent, and responsible for their own learning process. Therefore, schools and teachers are advised to continue developing learning approaches that can enhance independent learning in order to achieve optimal learning outcomes, particularly in Informatics at SMP Kristen Citra Bangsa Kupang.